2023
DOI: 10.3390/jmse11010150
|View full text |Cite
|
Sign up to set email alerts
|

Particulate Matter (PM1, 2.5, 10) Concentration Prediction in Ship Exhaust Gas Plume through an Artificial Neural Network

Abstract: In the last decade the reduction of carbon dioxide emissions in the transport sector, including the marine sector, has become the direction of its strategic development. Increased air pollution in the air is one of the main reasons for premature deaths around the globe. It was determined that while many methods provide adequate information about pollution levels, improvements could be made to avoid major errors. The traditional methods are either expensive or require a lot of data and human resources to correc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…Ship emission detection technologies play a critical role in reducing the impact of ship emissions on the environment and public health [3]. Ship emission detection technologies are still developing, and future research should focus on improving the technology's accuracy, efficiency, and cost-effectiveness [18]. Drones equipped with sniffing technology have been tested and applied to detect atmospheric pollution on ships.…”
Section: Ship Emission Detectionmentioning
confidence: 99%
See 3 more Smart Citations
“…Ship emission detection technologies play a critical role in reducing the impact of ship emissions on the environment and public health [3]. Ship emission detection technologies are still developing, and future research should focus on improving the technology's accuracy, efficiency, and cost-effectiveness [18]. Drones equipped with sniffing technology have been tested and applied to detect atmospheric pollution on ships.…”
Section: Ship Emission Detectionmentioning
confidence: 99%
“…The research problem includes ship emission detection methods, detection accuracy optimization, and detection effectiveness evaluation. Research methods related to ship detection issues include neural networks [18], simulation analysis [19], machine learning [20], optimization [21], and utilizing data such as Automatic Identification System (AIS) data [22], satellite images, and videos. Detection methods involve remote sensing, onboard measurement [23], and imaging pattern recognition [24].…”
Section: Ship Emission Detectionmentioning
confidence: 99%
See 2 more Smart Citations
“…Monitoring the emissions of pollutants from ships in port areas has a crucial impact on local environmental protection [1] . However, after reviewing the literature, it was found that most studies only roughly estimate ship pollutant emissions as part of the pollution sources in port cities [2] , without considering the accuracy of predicting optimized ship pollutant emissions. Current research on ship pollutants mainly focuses on utilizing Automatic Identification System (AIS) data, which provides real-time ship navigation information, and then using the Ship Traffic Emission Assessment Model (STEAM) developed by the Finnish Meteorological Institute (FMI) to calculate emissions [3] .…”
Section: Introductionmentioning
confidence: 99%